Jakościowe aspekty badań nad czasem wolnym współczesnych Polaków - Bombol, Małgorzata (Qualities Aspects of Leisure Measurement in Poland, 2006)
Leisure is a complex of human need. Leisure satisfaction can be defined as the positive perception or feelings that an individual forms, elicits, or gains as a result of engaging in leisure activities and choices. It is the degree to which one is presently content or pleased with her general leisure experiences and situations. This positive feeling of pleasure results from the satisfaction of felt or unfelt needs of individuals. Time - use studies typically have a single focus: to study frequency and duration of human activities. Time - use surveys may ask respondents to report everything they did during 24 hours period along with some indication of the starting and stopping time of those actions. Focus group researches can improve our knowledge about leisure activities and choices. The purpose of this paper is to investigate the determinants of individual leisure satisfaction, and met model of leisure consumption in well - off Polish households.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1107, s. 471-477